2018
DOI: 10.1155/2018/7418140
|View full text |Cite
|
Sign up to set email alerts
|

Non-Fickian Solute Transport in a Single Fracture of Marble Parallel Plate

Abstract: Accurate prediction of solute transport processes in a fracture aquifer is an important task not only for proper management of the groundwater but also for pollution control. A key issue of this task is how to accurately obtain the experimental data and to analyze the solute transport in fracture in subsurface hydrology, which would greatly help us to understand the releasing mechanism and transport of the solute in a fracture. In this study, a fracture experiment is conducted in a laboratory based on previous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 29 publications
(37 reference statements)
0
9
0
Order By: Relevance
“…However, the fitting parameter β of the TPL in the CTRW was previously used as an indicator for non-Fickian transport processes [24] and linked to contact area and Hurst exponent. However, the obtained parameters by [24] and [25] for β were smaller than 2, which is also given as a limit by [56] for Fickian transport. Our study shows, that for values of β larger than 4, the ADE is a suitable description and differences between fitting parameters of CTRW and ADE are within the range of fitting accuracy.…”
Section: Discussionmentioning
confidence: 87%
See 4 more Smart Citations
“…However, the fitting parameter β of the TPL in the CTRW was previously used as an indicator for non-Fickian transport processes [24] and linked to contact area and Hurst exponent. However, the obtained parameters by [24] and [25] for β were smaller than 2, which is also given as a limit by [56] for Fickian transport. Our study shows, that for values of β larger than 4, the ADE is a suitable description and differences between fitting parameters of CTRW and ADE are within the range of fitting accuracy.…”
Section: Discussionmentioning
confidence: 87%
“…However, through the usually strong non-Fickian transport behavior indicated through multiple peaks and the long tailing of the BTC, the ADE often results in an insufficient match of the transport parameters [38]. Previous studies showed that the continuous time random walk (CTRW) method is able to reproduce those non-Fickian features superior to a fit of the ADE (e.g., [25,26]). The CTRW is based on a Laplace transformation of the ADE using a memory function M [54].…”
Section: Determination Of Transport Parametersmentioning
confidence: 99%
See 3 more Smart Citations